Evaluation of Personal Digital Assistant Acceptance in Nursing Education - hosain, Shatha; Saddik, Basema (Iraqi National Journal of Nursing Specialties, 2018)
Objective:To measure the acceptance level of the Personal Digital Assistance (PDA)’suse among nursing students as a tool of education in the Kingdom of Saudi Arabia. Methodology: Eighty-nine nursing students participated in this cross-sectional descriptive study by completing a questionnaire based on the Technology Acceptance Model (TAM) by Davis. Two dimensions were explored and evaluated; (1) the applicability of the TAM model in assessing this technology; and (2) the overall percentage of students’ agreement on the different TAM variables. Results: This study presented significant positive influence between all the casual elements in TAM and therefore have confirmed the applicability of the TAM model in this study. The largest influence was 32.2%of intentional behavior caused by the attitudes toward using the technology. Overall, 94.9% of students reported a positive attitude in the future utilization of PDA’s. Recommendations: The results of the study revealed a positive direction.An encouraging impact of the use of PDA’s in both classroom and clinical settings.Therefore, the researchers recommend to explore more areas of research in measuring the effect of utilization of such devices in improving health educational outcomes in both classroom and clinical setting